The Impact of Inquiry Process on the Cognitive Process Dimensions of Nontraditional Writing - Memiş, Esra Kabataş; Öz, Muhittin (Richtmann Publishing, 2014)
The aim of this study was to evaluate the renewed taxonomy of writing to learn activities in terms of cognitive process dimensions. For this reason, 26 university students, who were at the 3rd year of their education and who studied the class of Education of Natural Sciences Laboratory Applications with the application of inquiry, were selected. These students had one writing to learn activity before and two writing to learn activities after the start of inquiry process. The first writing activity was related to the subject of “nuclear power”, and the last writing activities were related to “biofuel” and “power”. The sentences on the writing to learn activities were coded according to the cognitive dimensions of revised taxonomy and the resulting findings were evaluated in a comparative way. The results showed that the sentences at a low cognitive level reduced and the ones at the middle and high cognitive level increased on the last writing activities. Moreover, while the students who experienced the inquiry process emphasized the sentences reflecting the application regarding the scientific issues, they used high cognitive level sentences regarding the socio-scientific issues. DOI: 10.5901/mjss.2014.v5n20p1158
Keywords: 4. Education; 3. Good health